Reformasi Polri: Menilik Keberhasilan Program Presisi Polri - Edi Saputra Hasibuan (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
Success is not something that can be said or can be achieved easily, there is a benchmark that makes something successful, so for the National Police of course this can be seen through the level of public satisfaction with their performance, changes in handling models, progress in the law enforcement system, and improvement in the quality of resources, as well as several other factors. The emergence of the Precision program by the Chief of the National Police General Listyo Sigit is an illustration and a real example that this institution continues to transform consistently towards a better direction, of course this is not an easy matter, because every effort will find obstacles in it, the existence of this Precision program also aims to make the performance of the National Police more optimal for the community, for that this research tries to highlight how this Precision program has a real impact on the community and The National Police themselves, of course, and see the results of a hard work in order to realize a humane civilian police.